Relationship between decision-making self-efficacy, task self-efficacy, and the performance of a sport skill - Hepler, T. J.; Chase, M. A. (Journal of Sports Sciences, 2008)
The purpose of this study was to examine the relationships between decision-making self-efficacy and task self-efficacy and subsequent decision-making and task performance. Sixty undergraduate students (30 males, 30 females) participated in this study, which involved infield defensive plays in softball. The physical task required participants to throw a ball at a target. The decision-making task required participants to watch video scenes depicting different infield defensive situations and decide where to throw the ball in each situation. Both tasks used manipulated failure. Self-efficacy was assessed before performance. Strength of decision-making and task self-efficacy predicted physical performance, but not decision-making performance.